2017
DOI: 10.1186/s12889-017-4496-0
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of smokers’ perceptions about lung cancer screening

Abstract: BackgroundIn 2013, the US Preventive Services Task Force (USPSTF) began recommending lung cancer screening for high risk smokers aged 55–80 years using low-dose computed tomography (CT) scan. In light of these updated recommendations, there is a need to understand smokers’ knowledge of and experiences with lung cancer screening in order to inform the design of patient education and tobacco cessation programs. The purpose of this study is to describe results of a qualitative study examining smokers’ perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…Our finding that participants and HCPs held a belief in screening as something that saves lives and expressed trust in medicine are supported in the literature 25 26. Thornton et al ,26 reported that medical imaging is perceived as highly beneficial, though some contrasting studies have reported a variety of levels of trust of medical systems 27 28. In the face of this overriding trust in screening, we found a degree of disregard of the harms as either uncommon or insignificant, thus suggesting that providing information about the harms is unlikely to deter most individuals from LCS.…”
Section: Discussionsupporting
confidence: 71%
“…Our finding that participants and HCPs held a belief in screening as something that saves lives and expressed trust in medicine are supported in the literature 25 26. Thornton et al ,26 reported that medical imaging is perceived as highly beneficial, though some contrasting studies have reported a variety of levels of trust of medical systems 27 28. In the face of this overriding trust in screening, we found a degree of disregard of the harms as either uncommon or insignificant, thus suggesting that providing information about the harms is unlikely to deter most individuals from LCS.…”
Section: Discussionsupporting
confidence: 71%
“…After analysis of the data, themes and subthemes were organized under each level of the Social Ecological Model (SEM), a framework identified by Food and Nutrition Services for SNAP education and also used in other studies to address barriers to health. 23,24 The SEM addressed barriers that arose across themes and between the 4 communities collectively.…”
Section: Approachmentioning
confidence: 99%
“…[29][30][31][32][33][34] With regard to patients, there are gaps in awareness of screening criteria and availability. 35 A pragmatic trial is currently underway to investigate the impact of patient navigation on screening adherence, patient-reported barriers, psychosocial concerns, and smoking cessation. 36 A European position statement on lung cancer screening was published in Lancet Oncology in 2017, and for European centers starting a screening program, specific recommendations related to surgical management were recently published by a task force of the European Society of Thoracic Surgeons.…”
Section: Lung Cancer Screeningmentioning
confidence: 99%